2000
DOI: 10.1002/1529-0131(200004)43:4<894::aid-anr22>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of erythrocyte membrane fluidity, lipid composition, and lipid peroxidation in systemic sclerosis: Evidence of free radical–mediated injury

Abstract: Our findings support the idea that oxidative injury occurs in SSc and that, through lipid peroxidation, it induces structural and functional changes of the EM that may contribute to the development of the microvascular abnormalities that are seen in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 36 publications
(49 reference statements)
1
32
0
Order By: Relevance
“…Considering that PUFAs are the fatty acids most susceptible to oxidative damage, and that their relative concentration could be considered as an indirect marker of membrane lipid peroxidation (Frei et al 1988;Grandjean et al 1998;Suarez et al 1999;Solans et al 2000;Griffiths et al 2001), an increase in PUFAs suggests that despite a presumable increase in ROS production, peroxidative erythrocyte damage was prevented, probably due to enhanced antioxidant capacity of RBCs. However, since in our study the climbers' nutritional regimen was not controlled, it cannot be established whether or not these results were also due to significant changes in dietary habits, favouring the increased consumption of lipid-rich macronutrients, which could compensate an eventual increase in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that PUFAs are the fatty acids most susceptible to oxidative damage, and that their relative concentration could be considered as an indirect marker of membrane lipid peroxidation (Frei et al 1988;Grandjean et al 1998;Suarez et al 1999;Solans et al 2000;Griffiths et al 2001), an increase in PUFAs suggests that despite a presumable increase in ROS production, peroxidative erythrocyte damage was prevented, probably due to enhanced antioxidant capacity of RBCs. However, since in our study the climbers' nutritional regimen was not controlled, it cannot be established whether or not these results were also due to significant changes in dietary habits, favouring the increased consumption of lipid-rich macronutrients, which could compensate an eventual increase in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species can also increase vascular smooth muscle differentiation, leading to a more contractile phenotype of these cells [49]. Several studies have demonstrated evidence of oxidative stress by various methodologies in SSc [47,[50][51][52][53]. Specifically, one recent study noted increased urinary F2-isoprostanes in the urine of SSc patients and this associated with nailfold capillary pattern and lung disease severity [54].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Under oxidative stress PUFAs are highly susceptible to lipid peroxidation (Solans et al, 2000). Lipid peroxidation is a well-established mechanism of cellular injury and is used as an indicator of oxidative stress in cells and tissues (Magni et al, 1994).…”
mentioning
confidence: 99%